Gambaran Perencanaan dan Pengadaan Obat Di Rumah Sakit Umum Daerah Daya Kota Makassar - Molou, Muh Dwi Septian; Mustapa, Mohamad Adam; Uno, Wiwit Zuriati; Rasdianah, Nur; Papeo, Dizky Ramadhani Putri (-, 2026)
Drug planning and procurement in hospitals are two essential stages in the pharmaceutical supply management system, aimed at ensuring the availability of medicines with the right type, the right quantity, timely delivery, and cost efficiency. This study is based on the importance of effective and efficient pharmaceutical logistics management in ensuring the availability of medicines that meet the healthcare service needs of hospitals. Suboptimal drug management can negatively affect hospitals both medically and economically. The purpose of this study was to describe the drug planning and procurement processes at Daya Regional General Hospital in Makassar City. This research employed a qualitative descriptive method, with data collected through in-depth interviews, direct observation, and document review related to drug planning and procurement. The study sample consisted of the Head of the Pharmacy Installation, Warehouse Coordinator, and the Officers in charge of Inpatient and Outpatient services who are directly involved in the planning and procurement process. Data analysis was conducted descriptively by reviewing the results of interviews and field observations. The findings indicate that the drug planning process at Daya Regional General Hospital Makassar is carried out using a combination of consumption-based and epidemiological methods. The consumption method is based on analyzing drug needs, stock inflow and outflow, and average usage patterns, while the epidemiological method refers to disease case data from previous periods. Drug procurement is conducted through three systems: e-purchasing, direct purchasing, and tendering, with funding sourced from BLUD and APBN. The study concludes that drug planning and procurement at Daya Regional General Hospital Makassar have been implemented in accordance with applicable guidelines, although several operational challenges remain. Strengthening coordination among units, optimizing the e-purchasing system, and improving pharmaceutical logistics management are required to ensure better drug availability and enhance the quality of healthcare services.